2014
DOI: 10.4236/msa.2014.513094
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Thermal Behavior of High-Density Polyethylene (HDPE) at Different Temperatures

Abstract: In the present work, rheological properties of HDPE samples were measured at temperatures of 150˚C, 190˚C and 230˚C. It was shown, by oscillatory tests, at low frequencies, that, for temperatures of 150˚C and 190˚C, there was a predominance of the viscous behavior over the elastic one. At 230˚C, there was a predominance of the elastic contribution, and there was an increase of the molar mass compared with the ones obtained from the tests at 150˚C and 190˚C. The results obtained from the temperature ramp oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Frequency sweep rheological measurements were performed between 0.1 and 500 rad/s at 5% strain and at a melt temperature of 160 °C to avoid thermal degradation. 45 We observe increased complex viscosity (η*) with increasing Đ among the samples of each addition rate profile set (Figure S8). This is consistent with previous work which has shown that broadening the MWD of polymer melts enhances shear thinning to drastically lower the viscosity at high frequencies.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Frequency sweep rheological measurements were performed between 0.1 and 500 rad/s at 5% strain and at a melt temperature of 160 °C to avoid thermal degradation. 45 We observe increased complex viscosity (η*) with increasing Đ among the samples of each addition rate profile set (Figure S8). This is consistent with previous work which has shown that broadening the MWD of polymer melts enhances shear thinning to drastically lower the viscosity at high frequencies.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Oxidation was expected to create oxygenated groups in the fiber structure via radical mechanism, in type of R·, RO·, or ROO· groups. However, the inability of the polymer chain to obtain the esterified-like structure of ROO· did not promote the increase of molecular weight (Mw) or any kind of crosslinking; thus, the fibers melted during oxidative thermal stabilization treatment [22].…”
Section: Sulfonation and Crosslinking Mechanismsmentioning
confidence: 99%
“…Heat treatment of the formatted hydrocarbon polymer with polyacetylenic species and sulfonic acid groups in a temperature range from 100 • C to 180 • C results in desulfonation along with crosslinking among the hydrocarbon polymers and the formation of aromatic structures (reaction 4). Furthermore, heat treatment over 600 • C in inert atmosphere results in the formation of a graphite structure [22].…”
Section: Preparation Of Carbon Fibers (Cfs)mentioning
confidence: 99%
“…Although, lignin was on the scope of polymer scientists for years, its implementation into polymer science and engineering is often hindered by its structure, which is highly dependent on the extraction procedure and the type of plant selected [5,6]. On the other hand, nylon is widely used at a galore of everyday applications such as polymeric films, plastic bags and other products [7][8][9]. Several major industries over the world, such as the automobile industry, are constantly searching for materials with desirable and favorable properties in order to enhance their products and be more competitive in a global scale.…”
Section: Introductionmentioning
confidence: 99%